Randomized controlled pilot trial of a hand-held patient-oriented, insulin regimen optimizer. - Holman, R; Smale, A; Pemberton, E; Riefflin, A; Nealon, J (1996)
A robust, hand-held, patient-oriented insulin regimen optimizer (POIRO) has been developed. Relevant information is entered by selecting appropriate items from choices displayed on a touch-sensitive screen rather than a conventional keyboard. All data items are recorded, together with their time and date of entry, and may be recalled at any time with glucose values displayed graphically to provide an overview of glycaemic control. When requested, an integral, hybrid, statistical and rule-based expert system program uses all available data to suggest an optimum insulin dose within physician determined, pre-set limits. POIRO has been formally evaluated in a randomized crossover pilot trial, comparing two 3 week periods with and without decision support, in six patients with type 1 diabetes. Mean (SE) pre-prandial blood glucose levels were significantly lower during the period when decision support was available (7.5 (0.4) versus 8.9 (0.4) mmol/l, p = 0.015) with no increase in the frequency or severity of hypoglycaemia. The device, which was well received by the patients, may offer a relatively inexpensive method of providing expert diabetic advice at a distance. The persistence of improved glycaemic control, even after decision support was switched off, suggests the device could be used intermittently by patients and may have educational value.